The Role of CD4+ T Follicular Helper Cells in HIV Infection: From the Germinal Center to the Periphery - Thornhill, John Patrick; Fidler, Sarah; Klenerman, Paul; Frater, John; Phetsouphanh, Chansavath (Frontiers in Immunology, 2017)
T Follicular helper cells (TFh) are key components of the adaptive immune system; they reside in germinal centers (GC) where their interaction with B cells supports humoral immune responses and efficient antibody production. They are defined by the expression of CXCR5, PD-1, ICOS, and secretion of IL-21. Their differentiation is regulated by Bcl-6. The relationship and function of circulating TFh to bona fide TFh resident in the germinal center is much debated. HIV infection impacts the TFh response with evidence of aberrant TFh function observed in acute and chronic infection. Effective TFh responses are associated with the development of broadly neutralizing antibody responses to HIV and may be important for viral control. In addition, TFh are preferentially infected and act as a key reservoir for latent HIV infection. This review explores recent developments in our understanding of TFh differentiation, regulation, function and the relationship between cTFh and those in GCs, and the complex interaction between TFh and HIV infection.